Observation of Voriconazole in the Treatment of Liver Failure Complicated With Invasive Pulmonary Fungal Infection Induced by Chinese Patent Medicine in Teenagers: 2 Case Reports - Qian Su; Jinjin Pan; Li Zhang; Lingling Xia; Yufeng Gao; Jiabin Li (Frontiers Media S.A., 2022)
Background: Drug-induced liver injury (DILI) caused by Chinese patent medicines is increasing in China. The incidence of invasive fungal infections (IFIs) is increasing due to the suppression of the immune function in greater numbers of patients. Invasive procedures such as deep vein catheterization and the use of glucocorticoids are also predisposing factors to IFIs. The clinical presentation of IFI in teenagers is often atypical, challenging to diagnose, difficult to treat, and associated with a high fatality rate.Case presentation: Herein, we report 2 teenagers with liver failure after receiving oral Chinese patent medicines. Case 1 was a 14-year-old boy who presented with subacute liver failure who had been administered a Chinese patent medicine that included acetaminophen. Administration of glucocorticoids and non-bioartificial liver treatment improved his condition. Subsequently, invasive pulmonary Aspergillus (IPA) was diagnosed and was successfully treated with voriconazole for 85 days. Case 2 was a 17-year-old girl who presented with acute liver failure after taking the Chinese patent medicine QubaiBabuqi tablets for vitiligo. Chest computed tomography (CT) revealed multiple pulmonary nodules with an intermittent low-grade fever, and she was diagnosed with IPA. She was initially treated with caspofungin (23 days) and then voriconazole (406 days) for 429 days. Her liver function returned to normal, and lung lesions were absorbed in 2 patients. At the same time, two to three histopathological examinations of the liver biopsy showed that the drug-induced autoimmune-like phenomena could be improved by glucocorticoid therapy.Conclusion: To the best of our knowledge, this is the first report of the successful treatment of 2 cases of liver failure (Child-Pugh class C) caused by Chinese patent medicines complicated with IPA in teenagers. Drug-induced autoimmune-like phenomena could be improved by glucocorticoid therapy.